Kantari Festival: A Case study of Nawalpur District - Gurau , Deepak (Nepalese Culture, 2026)
This research article presents a comprehensive study of the Kantari festival which is celebrated every five years in Nawalpur district (Bardaghat Susta East) dedicated to the goddess Kuwarvarti Mai. Kuwarvarti Mai is a tutelary deity worshipped by the Tharu community of Nawalpur district as an ancestral goddess of power, protection and abundance. The study explores the rituals, traditions, and the syncretic relationship between the Tharu and Magar communities through this festival. It weaves every ritualistic fabric of this festival and delves into its specialty, attraction and uniqueness. It employs a qualitative research methodology, including semi-structured interviews with key informants, participatory observation, and analysis of primary and secondary sources. It documents the procession route of this festival across ten sacred places of worship locally known as thans, the esoteric rituals performed by Gurau priests using a divine sword called Khaand, and the vibrant performing arts integral to the celebration. The findings reveal that Kantari festival serves as a vital mechanism for preserving intangible cultural heritage, fostering communal solidarity, and maintaining the socio-religious structure of Nawalpur district. The syncretic blend between Tharu and Magar communities, manifested through shared worship and reciprocal ritual responsibilities is central to this festival. The article concludes that Kantari festival represents not merely a religious observance but a living cultural heritage that embodies nature worship, ancestral veneration, and the enduring spirit of communal harmony.